STUDI ETNOEKOLOGI MASYARAKAT ADAT TRAH BONOKELING DI BANYUMAS DAN CILACAP - Indah Anugrah Sari; Sulistijorini Sulistijorini; Yohanes Purwanto (Research Center for Biology-Indonesian Institute of Sciences, 2020)
The Bonokeling society is a part of the Javanese indigenous groups who still maintain and practise the local wisdom in their daily lives. Socio-cultural research concerning the Bonokeling religion has been reported and provided useful information to the society, while the ethnoecological studies about Bonokeling’s local knowledge related to the environment have not been reported. The research aimed to provide a comprehensive study about Bonokeling society on the management and utilization of natural resource and environment. This study used qualitative and quantitative approaches through participatory survey, open-ended interviews, and structured interviews with questionnaires. The results showed that the community recognized five environmental categorizations based on functions, namely settlements, home gardens, agricultural land, sacred sites, and irrigation sources. The plant diversity found were consisted of 288 species with 12 categories of uses. Pari is a species of cultivated plant that has the highest cultural importance value. The Bonokeling local knowledge can be scientifically proven has an ecological value. The management and utilization of agricultural land by the Bonokeling society have been carried out not only to optimize the production, but also provide the benefits to the environment. Besides, the management of sacred site has shown that traditional conservation practices have been maintained well for sustainability.